The Impact of Facebook on Early Marriage in Borok Toyang Village, West Sakra District, East Lombok Regency - Napis, Nurul Hapizatin; Masyhuri, Masyhuri Masyhuri; Nursaptini, Nursaptini Nursaptini (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The purpose of this study is to determine the impact of Facebook social media on early marriage in Borok Toyang Village, Sakra Barat District, East Lombok Regency. This study was conducted with a qualitative approach through a case study method. The data used in this study are primary data and secondary data with the research subjects being children who married early in the last one and a half years (2024-2025). Informants in this study were the Head of Borok Toyang Village, an Expert in Sociology, and the East Lombok Ministry of Communication and Information. The data collection technique in this study used the qualitative data analysis technique of the Miles and Humberman model with three stages: data reduction, data presentation and drawing conclusions/verification. The results of the study show that: There are impacts of Facebook social media that are often accessed by early childhood such as romantic content, wedding content, Korean dramas, traditional and cultural entertainment, to adult content that arouses high curiosity, addiction, and a high desire to do it in the real world so that children decide to marry early as a form of escape.